KHITANAN MASAL, CEK KESEHATAN GRATIS, JALAN SEHAT GRATIS DAN SENAM SEHAT (GERMAS) DI DESA LINGGAMUKTI KECAMATAN SUCINARAJA KABUPATEN GARUT - Hasbi Taobah Ramdani; Rudy Alfiyansah; Tantri Puspita; wahyudin; Iin Patimah; Andri Nugraha; Eldessa Vava Rilla (LP4M STIKes Karsa Husada Garut, 2020)
Health is a basic right for everyone regardless of the economic and social status of the community itself. In implementing health services for the community, there are still many obstacles. Health services have not been able to reach all citizens of the country, especially health services for poor people. The purpose of community service is to get used to living a healthy life at all times for the community, providing information and health services directly to the community. The method used is a social approach and the implementation of several social activities in order to improve the degree and quality of health in the Lingga Mukti Village area, Kec. Sucinaraja. Through healthy walking activities, mass circumcision and health checks accompanied by health education. The results obtained from community service activities, namely the participation of citizens following the healthy walk, namely as many as 200 people, namely 10% of the target to be achieved, healthy gymnastics activities from the target 10 groups obtained 4 groups who registered, the circumcision activity 6 participants who participated in mass circumcision 11 people who want to be achieved, the free health check activity from the target of 1000 participants 110 residents take the health check. For blood pressure checks, it was obtained from 110 residents whose blood pressure was checked, 20 people had high blood pressure, a blood sugar and uric acid check kit provided 2 devices and 50 sticks respectively. So, 50 people participated in the blood sugar check, 5 of whom had diabetes and a uric acid check was followed by 60 people, 5 of whom had uric acid above 6.5, and cholesterol tests from 50 residents 5 of them had low blood pressure and 10 had blood pressure above 120/80 , so the remaining sticks are 50 sticks of blood sugar and 40 sticks of uric acid.